Adverse effects of monoclonal antibodies in the treatment of moderate-to-severe asthma: a narrative review - Izabela Orzołek; Izabela Stawicka; Jakub Jarmołowicz; Agata Boczar; Patryk Dryja (Kazimierz Wielki University, 2024)
Introduction and purpose: Over the past two decades, the management of severe asthma shifted from high doses of inhaled and oral corticosteroids to targeted biologic agents. Adverse effects of treatment with monoclonal antibodies are not yet fully characterised. The aim of this paper is to provide a comprehensive review of the adverse effects of the FDA-approved monoclonal antibodies in the treatment of moderate-to-severe asthma, including omalizumab, benralizumab, dupilumab, mepolizumab, reslizumab, tezepelumab. Material and methods of research: A thorough literature review was performed using PubMed Web of Science and Embase, employing key words related to monoclonal antibodies, asthma and adverse effects. Description of the state of knowledge: Omalizumab and mepolizumab have black box warning on the risk of anaphylaxis. Due to scarcity of data, no causal association between the use of monoclonal antibodies and risk of malignancy can be established. The most common adverse effects of biologic agents in severe asthma include upper respiratory tract infections, nasopharyngitis and asthma worsening. Conclusions: Overall, monoclonal antibodies have a favourable safety profile, with certain risk of side effects remains present, and is variable for the different molecules. More studies of asthmatic patients treated with monoclonal antibodies are needed to spot rare adverse events and those developing over longer time.